Comparison of Clinical Symptoms and Severity of Sleep Disordered Breathing in Children with and without Cleft Lip and/or Palate. (September 2017) - Maclean, Joanna E; Fitzsimons, David; Fitzgerald, Dominic; Waters, Karen
Objective: To determine whether the clinical presentation or severity of sleep disordered breathing differs between children with or without a history of cleft lip and/or palate (CL/P) presenting for sleep assessment. Design: Retrospective chart review. Setting: Tertiary care pediatric hospital cleft clinic, sleep clinic. Patients: Children > 6 months of age presenting to the cleft clinic with sleep concerns and children without CL/P presenting to the sleep clinic in the same 2-year period. Main Outcomes Measures: Clinical symptoms and overnight polysomnography (PSG) results. Results: A total of 168 children (55 from cleft clinic, 113 from sleep clinic) were identified. Age at clinical review (6.6 ± 4.1 years versus 6.8 ± 4.0 years, P = ns), sex distribution (64.6% versus 58.4%, P = ns), and the presence of syndromes or significant medical conditions (12% versus 16%, P = ns) were similar between groups. Snoring was the reason for referral in 59% of children with CL/P and 69% of non-CL/P children ( P = ns). The only presenting feature that differentiated between the groups was a lower incidence of tonsillar enlargement in children with CL/P (33% versus 79%, chi-square 30.4, P < 0.001). Sleep study results showed similar apnea-hypopnea indices (6.2 ± 6.9 versus 7.9 ± 7.1 events/hr, P = ns) with more central apnea in children with CL/P (1.5 ± 1.5 versus 1.0 ± 1.0 events/hr, P = 0.017). Conclusions: Snoring and obstructive sleep apnea are common in CL/P with less tonsillar enlargement than non-CL/P children. Children with CL/P have similar OSA severity compared to non-cleft children but more central apnea which may indicate differences in the control of breathing.